A TRITERPENE ESTER SAPONIN FROM THE SEED OF Barringtonia asiatica - Rymond J Rumampuk; Emma J Pongoh; Ponis Tarigan; Anthony J Herlt; Lewis N Mander (Indonesian Journal of Chemistry, 2003)
A triterpene ester saponin has been isolated from the seed of Barringtonia asiatica and its structure has been established by extensive application of high-resolution FABMS and two dimensional NMR techniques to be 3-O-{[β-D-galactopyranosyl(1→3)-β-D-glucopyranosyl(1→2)]-β-D-glucuronopyranosyloxy}-22-O-[2-methylbutyroyloxy]-15,16,28-trihydroxy-(3β,15α,16α,22α)-olean-12-ene.